MBA education: new insights on enablers of managerial performance. Issue 6 (23rd February 2020) - Chatterjee, Debmallya; Poovathingal, James
Abstract : Purpose: Several authors have proposed various factors/enablers that enhance managerial performance of MBA students. However, there is little research on how to prioritise these enablers or how each enabler in the system of enablers influences each other. This paper aims to address this gap. Design/methodology/approach: This paper integrates the interpretive structural modelling (ISM) and Multiplication Appliquée á un Classement (MICMAC) techniques to arrive at the conclusions. Findings: The "help achieve" power of each enabler, determined by ISM, is limited or accentuated by its "driving power and its dependence" determined by MICMAC. Out of the 14 enablers used in the study, this paper identifies five enablers that can enhance the performance of MBA students. Research limitations/implications: When ISM and MICMAC are integrated, one can arrive at a better way to prioritise enablers in a system of enablers. Practical implications: The implication of the study findings is that all stakeholders can now systematically prioritise the enablers that can lead to performance and also save resources during the process. A related implication is that this method can be used in a wide variety of situations. Originality/value: This paper highlights how an integrated use of ISM-MICMAC can improve decision-making and resource optimisation.